Social Perception of Zoos and Aquariums: What We Know and How We Know It - Ana Villarroya; Rafael Miranda; Andrea Pino-del-Carpio; María Casas (Animals)
Zoos and aquariums attract millions of visitors around the world. At the same time, the functions they fulfill and the way they do that have been subject to scrutiny from different fields of knowledge. The way societies perceive animals has evolved in recent decades and so has the social perception of institutions that work with them. This scoping review aims to gather studies from the last three decades that shade light on how current societies perceive zoos and aquariums. We selected papers describing quantitative studies published in English in peer-reviewed journals. We reviewed 71 works from different fields of knowledge. The proportion of female authors was noticeably higher than in general science. Most studies were carried out in culturally Western countries, a fact that constitutes a gap in knowledge from a global perspective. We also noticed an underrepresentation of aquariums and of children in the analyzed papers, and a need for more pre–post studies to ascertain the effect of a zoo or aquarium on its visitors. These conclusions point out interesting directions for future studies to help scientists, managers, and citizens design the future of these institutions.